Leading organizations : perspectives for a new era - Hickman, Gill Robinson (Los Angeles : SAGE Publications, 2010)
Organisations are shifting from hierarchical structures to more open networks of people co-operating to achieve interrelated goals. This volume provides a framework for examining issues pertaining to the leadership of these new organisations.
1. The Environment of New Era Organizations -- 2. Leadership Concepts and Theories -- 3. Shared Responsibility for Leadership -- 4. Impetus for Organizational Leadership -- 5. Culture : The Organization's DNA -- 6. Inclusion -- 7. Capacity Building -- 8. New Responsibilities of Organizational Leadership : Social Activism.
Includes bibliographical references and indexes.
Keywords: Organizational behavior; Organizational effectiveness; Leadership; Aufsatzsammlung